1988
DOI: 10.1007/bf00181941
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective assessments of the effects of flupentixol and benzodiazepines on human psychomotor performance

Abstract: The aim of this double-blind crossover trial was to compare the objective and subjective effects of flupentixol and lorazepam on human performance, and to reveal possible interactions between flupentixol and diazepam. Twelve healthy students received at 1-week intervals oral single doses of flupentixol 1 mg, flupentixol 2 mg, lorazepam 2.5 mg, placebo, and diazepam 15 mg alone and with flupentixol 1 mg. After the baseline measurements, the drugs were given in capsule form, and the tests were repeated 1.5, 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…As a whole, the two combinations studied impaired performance to about the same extent as had previously been found after 2 to 2.5 g lorazepam [19,25] or 15 mg diazepam + 100 mg remoxipride [27]. In the latter study, the remoxipride-induced increase in plasma prolactin was not modified by diazepam or by 0.8 g-kg-1 alcohol.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As a whole, the two combinations studied impaired performance to about the same extent as had previously been found after 2 to 2.5 g lorazepam [19,25] or 15 mg diazepam + 100 mg remoxipride [27]. In the latter study, the remoxipride-induced increase in plasma prolactin was not modified by diazepam or by 0.8 g-kg-1 alcohol.…”
Section: Discussionsupporting
confidence: 61%
“…This type of delayed effect is interesting [24] and could result from slow penetration of suriclone into the brain and occupation of its receptors. Since the RIA method used for the suriclone assay also responds to suriclone metabolites, we subsequently "bioassayed" (Mattila, unpublished data) the plasma samples for suriclone and zopiclone, in diazepam equivalents, with a direct radioreceptor assay [25]. It appeared that suriclone concentrations were low or even undetectable, and the levels were similar at 2 and 4 h. Saletu et al [26] found that suriclone 0.4 mg improved sleep quality whereas 0.2 mg did not.…”
Section: Discussionmentioning
confidence: 99%
“…The study of psychomotor performance and cognitive function confirmed the very marked sedative effect of lorazepam which is manifested by an increased reaction time and a decrease in tapping and number of correct responses to a mental arithmetic test (Seppala et al, 1976(Seppala et al, , 1982Dundee et al, 1979;File and Bond, 1979;Aranko et al, 1985;Curran et al, 1987;Grunberger et al, 1988;Mattila et al, 1988;Saletu et al, 1988). The greater sedative effect of lorazepam has, moreover, been confirmed, comparatively with clobazam, in a quantitative EEG study (Saletu et al, 1985).…”
Section: Discussionmentioning
confidence: 73%
“…The ability to share attention between two tasks is a requirement in many routine tasks, especially automobile driving, and so it is important to evaluate the effects of psychoactive drugs on this ability. The psychomotor impairing effects of benzodiazepines have also been noted on simple arithmetic tests, digit recall and matching-to-sample performance (Forrest & Galletly, 1988;Roache & Griffiths, 1987;Roache et al, 1990 (Forrest & Galletly, 1988;Gorenstein et al, 1990;Mattila et al, 1988a) but not by midazolam and lormetazepam on the morning following evening administration (Rettig et al, 1990 Where the exact formulation used in a study was described that information is included. Hindmarch (1975) (12) Nicholson (1979) An adaptive tracking task was used in this study to evaluate the effects of overnight administration of 10, 20 and 30 mg temazepam and morning administration of 10 and 20 mg temazepam.…”
Section: Trackingmentioning
confidence: 99%
“…These results indicate that the impairment measured in those studies was not simply a function of the subject's inability to perform the test because of loss of muscle control or some pure motor effect. Eventually doses were reached at which tapping rate was also impaired (Eves & Lader, 1989;Leigh et al, 1991;Mattila, 1988;Mattila et al, 1986Mattila et al, , 1988aPatat et al, 1988;Preston et al, 1988).…”
Section: Tapping Ratementioning
confidence: 99%